2016
DOI: 10.1016/j.athoracsur.2015.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Reoperation for Failed Antireflux Operations

Abstract: Patients undergoing revision antireflux operations have improved quality of life, relatively normal swallowing, and primary symptom resolution at a median of 20 months postoperatively. However, patients who undergo more than one reoperation have lower quality of life scores and less improvement in dysphagia, suggesting that other procedures such as Roux-en-Y or short colon interposition, should be considered after a failed initial reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 28 publications
0
9
1
1
Order By: Relevance
“…Failure after the first redo-fundoplication is 12-20% and reaches 40% in cases submitted to a second redo. The worst results have been reported in obese or Barrett´s esophagus patients 7 , 20 , 25 , 41 , 49 , 50 , 51 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Failure after the first redo-fundoplication is 12-20% and reaches 40% in cases submitted to a second redo. The worst results have been reported in obese or Barrett´s esophagus patients 7 , 20 , 25 , 41 , 49 , 50 , 51 .…”
Section: Discussionmentioning
confidence: 96%
“…The postoperative complications range from 15-27% and a long hospital stay may be required (6-58 days). The success rate after the first re-fundoplication is very variable ranging from 42 to 94% and decreases to 60% after the second re-fundoplication 3 , 7 , 20 , 23 , 25 , 28 , 34 , 35 , 45 , 46 , 51 , 52 , 53 . In addition, studies addressing long term outcomes have observed 27 to 41% of reflux recurrence with incomplete relief of symptoms in 12-50% of patients submitted to re-fundoplication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 However, revisional fundoplication is associated with a higher failure rate than primary fundoplication, with a risk of failure as high as 60 per cent at five years. 5,6 Moreover, patients undergoing revisional fundoplication face a higher rate of postoperative complications with each subsequent fundoplication. 7 A significant risk factor, which is likely the primary driver for the increased incidence of GERD in recent decades, is obesity.…”
mentioning
confidence: 99%